PVA coated glass substrates for acetone detection - Jali, Mohd Hafiz; Jahava, Marlina; Abdul Rahman, Muhammad Azizi; Md Johari, Md Ashadi; Ahmad, Aminah; Mohd Yusof, Haziezol Helmi; Johari, Siti Halma; Harun, Sulaiman Wadi; Thokchom, Siddharth (Penerbit Akademia Baru, 2024)
Technology advancement in photonics has progressively tailor human need in healthcare industries. Inventing a new medical device or application for the mental and health sectors have make disease diagnosis easier. Without prevention, the number of sufferers may rise quickly. Studies have identified a way to diagnose diabetes illness by measuring a person's acetone level. The existing blood test have inferiority in term of invasive and dangerous if not handled properly. In this report, acetone concentration has been detected using a simple, low-cost Polyvinyl Alcohol (PVA) coated glass substrate platform as a potential diagnosis tool for diabetes patient. Based on the experiment results, the proposed sensor exhibits exceptional sensing performances for acetone detection in term of sensitivity, linearity, repeatability, stability and hysteresis.